Efficacy of Endodontic Treatment for Endotoxin Reduction in Primarily Infected Root Canals and Evaluation of Cytotoxic Effects - de Oliveira, Luciane Dias [UNESP]; Talge Carvalho, Claudio Antonio [UNESP]; Carvalho, Alessandra Sverberi [UNESP]; Alves, Jessica de Souza; Valera, Marcia Carneiro [UNESP]; Cardoso Jorge, Antonio Olavo (Elsevier B.V., 2012)
Introduction: Endotoxins are one of the etiologic agents involved in the pathogenesis of apical periodontitis. The objectives of this clinical study were to investigate the effects of endodontic treatment by using different irrigants on endotoxins in root canals with pulp necrosis and apical periodontitis and to evaluate the cytotoxic effects. Methods: Thirty-six root canals were selected. Samples were collected before (S1) and after instrumentation (S2). The root canals were divided into 3 groups (n = 12) according to the irrigant combination used: CLX + LW, 2% chlorhexidine gel + calcium hydroxide (0.14%, limewater); CLX + PmB, chlorhexidine + polymyxin B; CLX (control), chlorhexidine + saline. The third sampling (S3) was performed after ethylenediaminetetraacetic acid and S4 after intracanal medication (CLX + calcium hydroxide for 14 days). Endotoxins were quantified by the chromogenic Limulus amebocyte lysate assay, and cytotoxic effects were evaluated by the production of cytokines (interleukin-1 beta, tumor necrosis factor alpha) in macrophages (RAW 264.7) stimulated with the root canal content. Results: Endotoxins were detected in all root canals before instrumentation (S1). Group CLX + LW presented the greatest endotoxin reduction after instrumentation (99.18%), which was similar to group CLX + PmB (96.42%, P > .05) and different from group CLX (90.78%, P < .05). The intracanal medication promoted important endotoxin neutralization, with a reduction of 99.2% to 100%. The root canal content induced a higher production of tumor necrosis factor alpha and interleukin-1 beta in S1 samples compared with samples obtained after treatment. Conclusions: The combination of CLX and limewater as irrigant was the most effective in reducing endotoxins in root canals, and intracanal medication was important to neutralize the cytotoxic effects. (J Endod 2012;38:1053-1057)
Keywords: Calcium hydroxide; cytokines; endotoxin; macrophages; polymyxin B; root canal